The effectiveness of Facebook as a social network intervention to increase physical activity in Chinese young adults - Lau, Patrick W. C.; Wang, J. J.; Ransdell, Lynda L.; Shi, Lei (Frontiers in Public Health, 2022)
Introduction Physical inactivity is a global health problem. Meanwhile, the wide use of social network technology provides inspiration for researchers to conduct online social network interventions for PA promotion. Online social networks, such as Facebook are popular, easy to access and cost-effective, can be used to enhance individual’s PA participation. However, the effectiveness and features of online social network intervention is still unclear. The present study intended to identify the effectiveness and successful features of Facebook in young adults by reviewing relevant researches, and to examine how Facebook works to influence their PA. Method PubMed, Medline, SPORTDiscus, ERIC and Embase were searched from January 2005 to February 2022 to identify effectiveness and successful features of Facebook in PA intervention. Behavior modification strategies, influence agents, snowball grouping, social support, goal-setting, tailored feedback, and educational information are effective approaches to produce significant PA change outcomes. A 4-week Facebook and PA intervention was conducted to the university students. Objective PA measure and self-reported questionnaire were used to collect participants’ daily physical activity-related information and perceived PA level, stage of readiness, effectiveness and efficiency of Facebook. Results No significant difference was found in the Actigraph measurements between intervention and control groups, but the self-reported questionnaire reported has increased. More positive change in perceived stage of readiness in PA participation, commuting type, sport type, sport venue, sport emotion, fast breathing or sweating between two groups were reported. Finally, motivation (supports from your friends) and tailored feedback (the responses from your friends are really personal and fits you) are the top two features ranked by the intervention group. Conclusion The efficacy of Facebook and PA behavioral change intervention is examined in the present study. The finding demonstrated that no objective measured PA was found but the subjective perception of PA level and positive emotion were reflected. The use of influence agents could be an answer to their preference and higher program engagement. Significant differences of the commuting type, sport types, sport venue barriers, and exercise intensity between the intervention and control groups was indicated. These findings deserve a further investigation in the future.